Late Holocene Anthropogenic and Climatic Impact on a Tropical Island Ecosystem of Northern Vietnam - Briles, Christy; Serenchenko, Olga; Stevens, Lora; White, A. J.; Huong, Nguyen Thi Mai (Frontiers in Ecology and Evolution, 2019)
Northern Vietnam has a long history of human occupation, warfare, and agriculture; yet, the environmental consequences of human activity are poorly understood due to limited paleoecological records. Results from a terrestrial wetland sediment core from the tropical island, Quan Lan, in Ha Long Bay provide a local record of ecosystem responses to societal shifts due to warfare/instability and climate change. A multiproxy study, including pollen, macro charcoal, fecal stanols and geochemistry, suggests that native vegetation was abundant and low-level, subsistence wet-rice agriculture and burning were in practice during a time of increased monsoon intensity between 1150 BCE and 950 CE. Between 950-1450 CE, a trading and military port was established on Quan Lan Island which served as a major hub of southeast Asian trade and protected the mainland from Mongol invasions. During this period, population near the wetland declined to undetectable levels, rice agriculture declined, burning ceased, and disturbance species expanded. A simultaneous shift toward a more arid climate, with possible extended years of drought, occurred during the Medieval Climate Anomaly based on regional climate records. Without a reliable source of freshwater, rice production declined and/or was supplemented by trade. When the mainland capital near present day Hanoi moved south to Hue after 1450 CE, the port ceased operation. During this time, climate became wetter, and precipitation and surface water more reliable than before. Population near the wetland increased as did burning and rice agriculture. The research has implications for understanding the maintenance of tropical biodiversity amidst long-term human occupation, political unrest and climate change.